2013
DOI: 10.3748/wjg.v19.i35.5848
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic management of totally intra-thoracic stomach with chronic volvulus

Abstract: The laparoscopic management of IGV is a safe but technically demanding procedure. The best outcomes can be achieved in centers with extensive experience in minimally invasive esophageal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“…As a referral center for the surgical treatment of hiatal hernias [27, 28], after confronting with an ICT following laparoscopic anti-reflux surgery [2] (LARS), we conducted an in-depth analysis of the reported cases in peer-reviewed medical journals. The main aim of this review is to emphasize the importance of awareness for the prevention and better management of this extremely mortal, but avoidable complication.…”
Section: Introductionmentioning
confidence: 99%
“…As a referral center for the surgical treatment of hiatal hernias [27, 28], after confronting with an ICT following laparoscopic anti-reflux surgery [2] (LARS), we conducted an in-depth analysis of the reported cases in peer-reviewed medical journals. The main aim of this review is to emphasize the importance of awareness for the prevention and better management of this extremely mortal, but avoidable complication.…”
Section: Introductionmentioning
confidence: 99%
“…The use of inert material in this study, however, occurred selectively since it is a procedure with possible complications, and erosion of viscera is particularly concerning. 2 Zhang et al performed a systematic review and meta-analysis analyzing 11 studies (4 randomized, 9 non-randomized), comparing patients after surgical repair to reduce risk of recurrence and gastroesophageal reflux, employing mesh (n = 719) vs. suture (n = 755). They concluded that mesh repair of hiatus hernia compared to a suture repair alone, might be associated with less recurrences, and biological mesh improved quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence is not well defined in the literature because it is associated with gastric volvulus secondary to hiatal hernia. 2 The primary volvulus is described as those with flaccidity of stomach ligaments and secondary ones related to the presence of large hiatal hernias. 3 – 5 …”
Section: Introductionmentioning
confidence: 99%
“…It can present with gastric outlet obstruction, ischaemia and/or perforation 1 2. Borchardt’s triad of epigastralgia, retching and inability to pass a nasogastric tube are classical symptoms.…”
Section: Descriptionmentioning
confidence: 99%